Review of the literature on imaging diagnosis of dentigerous cyst - Castro Pesce, Rubén Alfredo (2019)
The dentigerous cyst, included in the classification of odontogenic cysts by the WHO in 2017, constitutes a relevant pathology in the bucco-maxillofacial area. Although its growth is slow and asymptomatic, when it reaches large dimensions, it has the capacity to cause bone destruction in jaws, which causes aesthetic and functional alterations. In addition, it has a high prevalence, with the odontogenic cyst as the most common, after the inflammatory radicular cyst. Radiology represents a fundamental tool in its diagnosis and many times its detection constitutes a radiographic finding. Normally, 2D techniques such as periapical, panoramic and occlusal radiography are used, which play a very important role in its detection and diagnosis. However, it must be considered that the similarity of the dentigerous cyst with other pathological processes, both clinically and radiographically, often leads to an inadequate diagnosis and treatment. This work aims to show whether the advent of new technologies such as magnetic resonance imaging and cone beam computed tomography allow improving the possibility of diagnosing the dentigerous cyst and distinguishing it from other lesions or pathologies with which the differential diagnosis is made.